Fighting bugs: Remove, retry, replicate, and rejuvenate - Grottke, Michael; Trivedi, Kishor (Computer, 2007)
Combatting vastly different types of software bugs requires different strategies.
WiSo-Import:2015-03-26:1361
Keywords: Innovation